POSITIONING OF ART TOURISM IN THE OVERALL STRUCTURE OF TOURISM - SYVENKO, Anton (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. The problem of positioning art tourism in the structure of tourism is studied and the necessity of its allocation as an independent type of cultural tourism is substantiated. The relevance of the research topic is determined, which is due to the growing demand for specialised tourism products, among which art occupies an important place, which can act as a driving force for the development of tourist attractiveness of regions and destinations. Methods. The study uses the methods of logical analysis, systematic approach, comparative analysis of scientific publications, and the method of graphic systematisation to create a table of art tourism positioning. Results. Based on the analysis of scientific sources, the insufficient theoretical conceptualisation of art tourism is revealed, which complicates its integration into the development strategies of territories. It has been established that in modern scientific discussions art tourism is positioned mainly as a component of cultural tourism, although its specificity is determined by the active interaction of tourists with the artistic environment, which goes beyond the traditional passive contemplation. Based on the generalisation of existing classifications, the author proposes his own definition of art tourism as a type of cultural tourism, formed at the intersection of museum, creative and heritage tourism, which uses creativity as a resource potential for creating unique tourist products. A graphical model has been developed that visualises the place of art tourism among other types of cultural tourism. Recommendations for the creation of art tourism products with the integration of museum exhibitions, art events, historical and cultural resources and creative practices have been formulated, which provides aesthetic, educational and emotional experience for tourists.Conclusions. The obtained results suggest that the development of art tourism should focus on the integration of various cultural and artistic resources with the active use of creative potential, which is an important factor in increasing the tourist attractiveness of regions and their competitiveness. The prospect of further research may be the development of clear indicators and methods for assessing the effectiveness of art tourism, as well as more detailed applied recommendations for managing this type of tourism activity at different levels of the organization.
Keywords: art tourism; cultural tourism; museum tourism; creative tourism; tourism industry